Innovation of Islamic Education (PAI) Based on Multiple Intelligences - Abdul Basid (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2017)
This article explores Islamic education based on multiple intelligences. Islam requires human orientation not only on the outcome but also the quality of process. It has been commonly known for several decades that the major experts in education use only intelligence quotient (IQ) tests as the sole measure in